Store Choice Behavior for Groceries: a Comparative Study - Zunaith Ahmed, Dr.; ., . (International Journal of Engineering and Technology, 2018)
The Indian retail industry has experienced revolutionary changes in the last decade. Most of the challenges are due to the changing demographic, social, political, business climate and changes in the retail sector. How consumers respond to changing retail formats is reflected in their retail shopping behavior. The purpose of this study was to investigate store choice behavior for groceries in Chennai city; a questionnaire based on the literature review was designed. The questionnaire covered two parts, Part I contains questions on the Personal profile. Part II of the questionnaire had rating scale statements, multiple choice questions and dichotomous questions reflecting the store choice behavior. The researcher used Chi-square analysis to find if any significant association exists between the Store choice behavior and the Customers demographic profile. The researcher identified that the following factors like frequency of purchase, time spent for shopping, mode of payment, shopping list and shopping enjoyment and place of shopping are found to be associated with store choice behavior.Â Â